Staff and patient perceptions of seclusion: has anything changed? - Meehan, T; Bergen, H; Fjeldsoe, K (2004)
BACKGROUND: Seclusion continues to be widely used in the management of disturbed behaviour in hospitalized patients. While early research on the topic highlighted significant differences in staff and patient perceptions, there are few recent data to indicate if these differences still exist. AIM: This paper reports a study exploring the perceptions of both nursing staff and patients towards the reasons for seclusion; its effects; patients' feelings during seclusion; and possible changes to the practice. METHODS: Sixty nursing staff and 29 patients who had experienced seclusion at three inpatient units in Queensland, Australia completed Heyman's Attitudes to Seclusion Survey. RESULTS: The findings indicate that the two groups differed significantly on a number of the dimensions assessed. Nurses believed seclusion to be very necessary, not very punitive and a highly therapeutic practice that assisted patients to calm down and feel better. Patients, on the other hand, believed that seclusion was used frequently for minor disturbances and as a means of staff exerting power and control. Patients also believed that seclusion resulted in them feeling punished, and had little therapeutic value. CONCLUSION: The disagreement between staff and patients highlights the need for greater dialogue between these groups. While nursing staff require greater understanding of how patients feel about seclusion, patients require information on why and how seclusion is implemented.